APPLICATION OF ARCS-BASED PROBLEM BASED LEARNING IN IMPROVING MATHEMATICS LEARNING OUTCOMES ON TWO-VARIABLE LINEAR EQUATION SYSTEM FOR GRADE VIII A STUDENTS SMPN 1 BUNGAH GRESIK - Sugiarti Sugiarti (LPPM STAI Muhammadiyah Probolinggo, 2022)
Teaching and learning are conducted through gradual procedures beginning at uncomplicated materials and ending at more complex topics. This is to avoid the assumption that learning process at school is very difficult, especially math subjects. For students of SMPN 1 Bungah Gresik, many students complain that mathematics subjects are scary, unattractive and difficult; it does not seem to be related to everyday life. This reality is a negative perception of mathematics. Meanwhile, there are also students who enjoy the preoccupation of mathematics and are challenged to solve every math problem. This reality is a positive perception of mathematics.The application of the Problem Based Learning learning model with the ARCS motivation strategy can improve student learning outcomes and mathematics learning motivation in Class VIII A SMPN 1 Bungah Gresik for the 2018/2019 academic year to meet the achievement indicators in cycle II, namely 64.29% of students have high category motivation. Based on the results of observations of learning motivation, the percentage of students' learning motivation in the low category pre-cycle was 25%, the medium category was 35.71% and the high category was 39.29%. In the first cycle, the percentage of students' motivation to learn mathematics in the low category was 11.71%, the medium category was 39.29% and the high category was 50%. In the second cycle, the percentage of learning motivation in the low category was 0%, the medium category was 35.71% and the high category was 64.29%.